Preparation method and application of high-performance concrete

By combining modified silica fume, ultrafine steel slag particles and polyether polyol modified epoxy resin, the preparation process is optimized, and the existing high-performance concrete has poor balance and production complexity problems have been solved, and high strength, durability and volume stability have been improved.

CN119797845APending Publication Date: 2025-04-11HUIZHOU ZHENGDA CONCRETE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016268.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

While improving some properties, existing high-performance concrete often leads to degradation of other properties, and lacks durability in complex environments, poor volume stability, complex production processes and high cost.

Method used

By innovatively combining a variety of functional components, including modified silica fume, ultrafine steel slag particles and polyether polyol modified epoxy resin, an optimized preparation process is adopted to achieve a comprehensive improvement in concrete performance.

Benefits of technology

The perfect combination of ultra-high strength and excellent durability is achieved, which significantly improves the resistance to seepage, corrosion resistance and dimensional stability, while simplifying the production process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230019210000191
    Figure BDA0005230019210000191
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to a preparation method and application of high-performance concrete, (1) preparation of a fine admixture, (2) preparation of modified silica fume, (3) preparation of superfine steel slag particles, (4) preparation of polyether polyol modified epoxy resin and (5) preparation of the high-performance concrete, and perfect combination of ultrahigh strength and excellent durability is realized. Active SiO2 in the modified silica fume and CaO provided by the superfine steel slag particles form a large amount of high-quality C-S-H gel in the hydration process, the strength of the concrete is remarkably improved, the microstructure of the concrete is optimized, the anti-permeability and erosion resistance are improved, the polyether polyol modified epoxy resin is introduced, interface bonding is enhanced, and microcracks are filled, so that the anti-corrosion performance of the concrete is improved, and the anti-corrosion performance of the concrete is improved. The overall performance and durability of the concrete are improved; the concrete shows excellent environmental adaptability; in a chloride ion penetration test, the charge flux is obviously lower than that of the traditional high-performance concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a preparation method and application of high performance concrete. Background Art

[0002] With the rapid development of modern architecture and infrastructure, the requirements for concrete performance are also increasing. Traditional ordinary concrete can no longer meet the needs of some special projects, such as super high-rise buildings, marine engineering, nuclear power plants, etc. Therefore, the research and application of high-performance concrete has become a hot topic in the field of concrete technology in recent years.

[0003] At present, the research on high-performance concrete mainly focuses on improving strength, improving durability and optimizing working performance. Common improvement methods include using mineral admixtures, introducing fiber reinforcement, optimizing aggregate grading, etc. However, while these methods improve certain properties, they often lead to the decline of other properties. For example, the pursuit of high strength alone may increase the brittleness of concrete and reduce durability; excessive use of mineral admixtures may reduce the early strength and working performance of concrete; and although the introduction of fibers can improve toughness, it may also bring problems such as poor dispersion and increased cost.

[0004] In addition, existing high-performance concrete still has shortcomings when facing complex environments. For example, under extreme conditions such as chloride ion penetration, freeze-thaw cycles and sulfate erosion, the durability of many high-performance concretes still cannot meet engineering requirements. At the same time, the volume stability problem of high-performance concrete has always been a problem that plagues engineering applications. Excessive shrinkage deformation may cause structural cracks and affect service life.

[0005] Another important issue is that the existing high-performance concrete formula is often too complicated and the preparation process is cumbersome, which not only increases the production cost but also limits its large-scale application. How to simplify the process while ensuring the high performance of concrete has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the above problems, the present invention proposes a preparation method and application of a new type of high-performance concrete. The method achieves a comprehensive improvement in concrete performance by innovatively combining multiple functional components and adopting an optimized preparation process.

[0007] The object of the present invention is to provide a method for preparing high performance concrete, comprising the following steps:

[0008] (1) Preparation of fine admixture:

[0009] 50-100 parts by weight of slag powder with a particle size of 50-100 mesh, 15-25 parts by weight of kaolin with a particle size of 500-700 mesh, 5-10 parts by weight of silica fume with a particle size of 3000-10000 mesh and 2-5 parts by weight of gypsum with a particle size of 100-300 mesh are mixed, 5-10 parts by weight of water are added, dry-milled in a ball mill at a rotation speed of 200-250 rpm for 2-3 hours, then wet-milled in a grinder at a rotation speed of 300-350 rpm for 1-2 hours, and finally dried at 60-80° C. for 4-6 hours to obtain a fine admixture;

[0010] (2) Preparation of modified silica fume:

[0011] Slowly add 100 parts by weight of silica fume to 50-70 parts by weight of a 98% sulfuric acid solution, stir and react at 60-70°C for 1-2 hours, cool to room temperature, add 10-15 parts by weight of γ-glycidyloxypropyltrimethoxysilane (KH-560), continue stirring for 0.5-1 hour, wash with 200-250 parts by weight of deionized water for 3-4 times until the pH reaches 5-6, and dry at 80-100°C for 6-8 hours to obtain modified silica fume;

[0012] (3) Preparation of ultrafine slag particles:

[0013] 100 parts by weight of steel slag and 200-250 parts by weight of zirconium balls or zirconium oxide balls are added to a planetary ball mill, dry-milled at a speed of 350-400 rpm for 4-6 hours, sieved through a 45 μm sieve, and particles with a particle size of <45 μm are collected;

[0014] (4) Preparation of polyether polyol modified epoxy resin:

[0015] First, 100 parts by weight of polyacrylate polyol (molecular weight 1000-2000), 5-10 parts by weight of sodium carbonate and 30-50 parts by weight of deionized water are mixed, and stirred at 100-120° C. for 2-4 hours;

[0016] Secondly, cool to 80-90°C, add 20-30 parts by weight of epoxy crosslinking agent and 15-25 parts by weight of polyamine crosslinking agent, and continue stirring and reacting for 3-5 hours;

[0017] Then, the above product is mixed with 200-300 parts by weight of bisphenol A diglycidyl ether (DGEBA), and stirred at 130-150° C. for 4-6 hours;

[0018] Again, the obtained product is mixed with 50-100 parts by weight of polyether polyol (molecular weight 1000-3000), and stirred at 70-90° C. for 6-8 hours;

[0019] Finally, adding 20-30 parts by weight of glycidyl methacrylate at 60-70° C. and continuing the reaction for 2-3 hours to obtain a polyether polyol modified epoxy resin;

[0020] (5) Preparation of high performance concrete:

[0021] Mix 300-350 parts by weight of cement (strength grade 42.5), 150-200 parts by weight of the fine admixture obtained in step (1), 600-650 parts by weight of coarse aggregate (particle size 5-20 mm), 500-550 parts by weight of fine aggregate (particle size 0.3-0.6 mm) and 150-180 parts by weight of water, and stir in a mixer at a speed of 60-80 rpm for 30-60 seconds;

[0022] Add 5-10 parts by weight of PVA fiber (0.22-0.66 dtex, 60-80 mm long) and stir for 60-90 seconds;

[0023] Add 3-5 parts by weight of polycarboxylic acid high performance water reducer and stir for 30-60 seconds;

[0024] Finally, add 10-20 parts by weight of the polyether polyol modified epoxy resin obtained in step (4) and stir for 90-120 seconds;

[0025] Pour the mixture into a mold and vibrate on a vibration table at a frequency of 50-60 Hz for 45-60 seconds;

[0026] The high performance concrete is obtained by curing for 28 days under the conditions of 20-25°C and relative humidity of 90-95%.

[0027] Specifically, in step (1), the specific surface area of ​​the slag powder is 400-450m 2 / kg, the specific surface area of ​​the kaolin is 15-20m 2 / g, the specific surface area of ​​the silica fume is 15-30m 2 / g.

[0028] Specifically, in step (2), the SiO 2 Content ≥85%.

[0029] Specifically, in step (3), the main chemical components of the steel slag are CaO 35-45%, SiO 2 30-40%, Al 2 O 3 10-15% and MgO 5-10%.

[0030] Specifically, in the step (4), the trade name of the polyacrylate polyol is Desmophen 1150 or Fomrez 55-112, the epoxy crosslinking agent is glycidyl ether, trade name Epikote 828 or DER 331, and the polyamine crosslinking agent is diethylenetriamine, trade name DETA or Duomeen O.

[0031] Specifically, in step (4), the polyether polyol is polypropylene glycol, with a trade name of Voranol or Jeffol.

[0032] Specifically, in the step (5), the trade name of the polycarboxylic acid-based high-performance water-reducing agent is MasterGlenium or SikaViscoCrete.

[0033] The method for preparing high performance concrete is characterized by further comprising the following steps:

[0034] The prepared high-performance concrete is poured into a formwork with a length of 3m. Adjacent formworks are connected with steel plates or angle steels. Tripods or temporary columns are added on the left and right sides of the formwork for support and fixed by adjusting cables. The formwork is retained at least 10cm outside the edges of the bottom surface of the concrete pouring bin on both sides, and the top of the formwork exceeds the upper edge of the pouring bin surface.

[0035] Specifically, the pouring step includes:

[0036] Use a concrete placing machine for pouring. The inclination angle between the concrete placing machine nozzle and the warehouse surface is 45°. The nozzle is 1.5m high from the warehouse surface. The lower edge of the nozzle is 0.5m away from the center line of the warehouse surface. Multiple nozzles are set on the conveying pipe of the concrete placing machine, and the nozzle arrangement spacing is 2m.

[0037] The material placing machine moves the material along the track at a speed of 0.5m / min, and adjusts the material placement position every 1.0m or so of material being unloaded.

[0038] The high-performance concrete prepared by the preparation method of the high-performance concrete is used in the preparation of protective structural coatings, wherein the protective structural coatings contain 50-65% by weight of the high-performance concrete, 25-37% by weight of water, 1-6% by weight of acrylic latex, 0.1-1% by weight of a defoamer, 0.1-1% by weight of a dispersant, 0.1-1% by weight of a stabilizer and 0.1-1% by weight of a leveling agent.

[0039] The beneficial effects of the present invention are mainly reflected in the following aspects:

[0040] First, the present invention achieves a perfect combination of ultra-high strength and excellent durability through the synergistic effect of multiple components. 2The CaO provided by the ultrafine steel slag particles forms a large amount of high-quality CSH gel during the hydration process, which not only significantly improves the strength of the concrete, but also optimizes its microstructure, and improves its impermeability and erosion resistance. At the same time, the introduction of polyether polyol modified epoxy resin further improves the overall performance and durability of the concrete by enhancing interface bonding and filling microcracks.

[0041] Secondly, the concrete of the present invention exhibits excellent environmental adaptability. In the chloride ion penetration test, the charge flux is significantly lower than that of traditional high-performance concrete, which is due to the dense microstructure formed by multi-graded fine admixtures and the barrier effect of polyether polyol-modified epoxy resin. In the freeze-thaw cycle and sulfate attack tests, the concrete of the present invention also performs well, which is attributed to its optimized pore structure and self-repairing ability.

[0042] Furthermore, the present invention solves the long-standing volume stability problem of high-performance concrete. Through a carefully designed multi-component formula, especially the synergistic effect of modified silica fume and ultra-fine steel slag particles, the free shrinkage rate of concrete is significantly reduced and the dimensional stability is improved, which is of great significance for the application of large-volume concrete structures.

[0043] Finally, the preparation method of the present invention simplifies the production process and improves the performance of concrete. The optimized step-by-step mixing process ensures the full dispersion and reaction of each component, maximizes the performance advantages of each material, which not only improves the overall performance of concrete, but also reduces the difficulty and cost of production, laying the foundation for large-scale application.

[0044] In general, the present invention has achieved comprehensive breakthroughs in strength, durability, environmental adaptability and process simplification through innovative formula design and preparation process, opening up a new direction for the development of high-performance concrete. It is expected to play an important role in special projects such as super-high-rise buildings, marine engineering, nuclear power plants, etc., and promote technological progress in the construction and infrastructure industries. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] In the high-performance concrete preparation method of the present invention, the trade name of the polyacrylate polyol is Desmophen 1150 (Covestro) or Fomrez 55-112 (Momentive), and the manufacturer is Covestro (Covestro), Momentive Performance Materials; the epoxy crosslinking agent (taking glycidyl ether as an example), the trade name is Epikote 828 (Hexion), DER 331 (Dow Chemical), the manufacturer is Hexion Inc., Dow Chemical (Dow Chemical), the polyamine crosslinking agent (taking diethylenetriamine as an example), the trade name is DETA (BASF), Duomeen O (AkzoNobel); the manufacturer is BASF (BASF), AkzoNobel (AkzoNobel); the polyether polyol, the trade name is Voranol (Dow Chemical), Jeffol (Huntsman); the manufacturer is Dow Chemical (Dow Chemical), Huntsman (Huntsman); the glycidyl methacrylate, the trade name is Glyma (Evonik), Miramer M100 (Miwon), manufacturer: Evonik Industries, Miwon Specialty Chemical; polycarboxylic acid-based high-performance water reducer, trade name: MasterGlenium (BASF), SikaViscoCrete (Sika); manufacturer: BASF, Sika.

[0047] Example 1

[0048] The high performance concrete preparation method of this embodiment comprises the following steps:

[0049] (1) Preparation of fine admixture:

[0050] First, 50 parts by weight of 50-mesh slag powder, 15 parts by weight of 500-mesh kaolin, 5 parts by weight of 3000-mesh silica fume, and 2 parts by weight of 100-mesh gypsum were mixed. The specific surface area of ​​the slag powder is 400 m 2 / kg, the specific surface area of ​​kaolin is 15m 2 / g, the specific surface area of ​​silica fume is 15m 2 / g. This combination can improve the strength and durability of concrete. Then, 5 parts by weight of water was added, dry-milled in a ball mill at 200 rpm for 2 hours, and wet-milled in a grinder at 300 rpm for 1 hour. Finally, dried at 60°C for 4 hours to obtain a fine admixture. This multi-stage grinding process can significantly improve the reactivity and dispersibility of the fine admixture.

[0051] (2) Preparation of modified silica fume:

[0052] 100 parts by weight of SiO 2 Silica fume with a content of 85% was slowly added to 50 parts by weight of a sulfuric acid solution with a concentration of 98%, and stirred at 60°C for 1 hour. After cooling to room temperature, 10 parts by weight of γ-glycidyloxypropyltrimethoxysilane (KH-560) was added and stirred for 0.5 hours. Subsequently, it was washed 3 times with 200 parts by weight of deionized water until the pH reached 5, and dried at 80°C for 6 hours to obtain modified silica fume. This modification can improve the activity and dispersibility of silica fume, thereby enhancing the strength and density of concrete.

[0053] (3) Preparation of ultrafine slag particles:

[0054] 100 parts by weight of a mixture containing 35% CaO, 35% SiO 2 40%, Al 2 O 3 Steel slag with 15% MgO and 10% MgO and 200 parts by weight of zirconium balls were added to a planetary ball mill and dry-milled at 350 rpm for 4 hours, sieved through a 45 μm sieve, and particles with a particle size of <45 μm were collected. This ultra-fine steel slag particle can be used as an active filler to significantly improve the strength and density of concrete.

[0055] (4) Preparation of polyether polyol modified epoxy resin:

[0056] First, 100 parts by weight of polyacrylate polyol with a molecular weight of 1000 (trade name: Desmophen1150), 5 parts by weight of sodium carbonate and 30 parts by weight of deionized water are mixed and stirred at 100°C for 2 hours. Secondly, the mixture is cooled to 80°C, 20 parts by weight of glycidyl ether (trade name: Epikote828) and 15 parts by weight of diethylenetriamine (trade name: DETA) are added, and the stirring reaction is continued for 3 hours. Then, the above product is mixed with 200 parts by weight of bisphenol A diglycidyl ether (DGEBA) and stirred at 130°C for 4 hours. Again, the obtained product is mixed with 50 parts by weight of polypropylene glycol (trade name: Voranol) and stirred at 70°C for 6 hours. Finally, 20 parts by weight of glycidyl methacrylate are added at 60°C and the reaction is continued for 2 hours to obtain a polyether polyol modified epoxy resin. This multi-step reaction can improve the compatibility and bonding strength of the modified epoxy resin with the cement matrix, thereby enhancing the mechanical properties of concrete.

[0057] (5) Preparation of high performance concrete:

[0058] Mix 300 parts by weight of cement of strength grade 42.5, 150 parts by weight of fine admixture obtained in step (1), 600 parts by weight of coarse aggregate with a particle size of 5 mm, 500 parts by weight of fine aggregate with a particle size of 0.3 mm and 150 parts by weight of water, and stir in a mixer at a speed of 60 rpm for 30 seconds. Add 5 parts by weight of PVA fiber (0.22 dtex, 60 mm long) and stir for 60 seconds. Then add 3 parts by weight of polycarboxylic acid high-performance water reducer (trade name: MasterGlenium) and stir for 30 seconds. Finally, add 10 parts by weight of polyether polyol modified epoxy resin obtained in step (4) and stir for 90 seconds. Pour the mixture into a mold and vibrate it on a vibration table at a frequency of 50 Hz for 45 seconds. Curing for 28 days at 20°C and relative humidity of 90% to obtain high-performance concrete.

[0059] Preferably, in the embodiments of the present invention, the addition of PVA fibers can significantly improve the toughness and crack resistance of concrete, while the polycarboxylic acid-based high-performance water reducer can improve the fluidity and workability of concrete, while reducing the water-cement ratio and improving the strength and durability of concrete.

[0060] Example 2

[0061] The high performance concrete preparation method of this embodiment comprises the following steps:

[0062] (1) Preparation of fine admixture:

[0063] 75 parts by weight of slag powder with a particle size of 75 mesh, 20 parts by weight of kaolin with a particle size of 600 mesh, 7.5 parts by weight of silica fume with a particle size of 6500 mesh, and 3.5 parts by weight of gypsum with a particle size of 200 mesh were mixed. The specific surface area of ​​the slag powder is 425 m 2 / kg, the specific surface area of ​​kaolin is 17.5m 2 / g, the specific surface area of ​​silica fume is 22.5m 2 / g. 7.5 parts by weight of water was added, dry-milled in a ball mill at 225 rpm for 2.5 hours, and wet-milled in a grinder at 325 rpm for 1.5 hours. Finally, dried at 70°C for 5 hours to obtain a fine admixture.

[0064] (2) Preparation of modified silica fume:

[0065] 100 parts by weight of SiO 2 Silica fume with a content of 90% was slowly added to 60 parts by weight of a sulfuric acid solution with a concentration of 98%, and stirred at 65°C for 1.5 hours. After cooling to room temperature, 12.5 parts by weight of γ-glycidyloxypropyltrimethoxysilane (KH-560) was added and stirred for 0.75 hours. The mixture was washed 3.5 times with 225 parts by weight of deionized water until the pH reached 5.5, and dried at 90°C for 7 hours to obtain modified silica fume.

[0066] (3) Preparation of ultrafine slag particles:

[0067] 100 parts by weight of a mixture containing 40% CaO, 40% SiO 2 35%, Al 2 O 3 Steel slag containing 15% of Ag and 10% of MgO and 225 parts by weight of zirconium oxide balls were added to a planetary ball mill and dry-milled at a rotation speed of 375 rpm for 5 hours, and sieved through a 45 μm sieve to collect particles with a particle size of <45 μm.

[0068] (4) Preparation of polyether polyol modified epoxy resin:

[0069] 100 parts by weight of polyacrylate polyol with a molecular weight of 1500 (trade name: Fomrez55-112), 7.5 parts by weight of sodium carbonate and 40 parts by weight of deionized water were mixed and stirred at 110°C for 3 hours. After cooling to 85°C, 25 parts by weight of glycidyl ether (trade name: DER 331) and 20 parts by weight of diethylenetriamine (trade name: Duomeen O) were added and stirred for 4 hours. The above product was mixed with 250 parts by weight of bisphenol A diglycidyl ether (DGEBA) and stirred at 140°C for 5 hours. The obtained product was mixed with 75 parts by weight of polypropylene glycol and stirred at 80°C for 7 hours. Finally, 25 parts by weight of glycidyl methacrylate were added at 65°C and the reaction was continued for 2.5 hours to obtain a polyether polyol modified epoxy resin.

[0070] (5) Preparation of high performance concrete:

[0071] 325 parts by weight of cement of strength grade 42.5, 175 parts by weight of fine admixture obtained in step (1), 625 parts by weight of coarse aggregate with a particle size of 12.5 mm, 525 parts by weight of fine aggregate with a particle size of 0.45 mm and 165 parts by weight of water are mixed and stirred in a mixer at a speed of 70 rpm for 45 seconds. 7.5 parts by weight of PVA fiber (0.44 dtex, 70 mm long) are added and stirred for 75 seconds. 4 parts by weight of polycarboxylic acid high-performance water reducer (trade name: SikaViscoCrete) are added and stirred for 45 seconds. Finally, 15 parts by weight of polyether polyol modified epoxy resin obtained in step (4) are added and stirred for 105 seconds. The mixture is poured into a mold and vibrated on a vibration table at a frequency of 55 Hz for 52.5 seconds. High-performance concrete is obtained by curing for 28 days at 22.5°C and a relative humidity of 92.5%.

[0072] In the embodiments of the present invention, by optimizing the composition and particle size distribution of fine admixtures, the bulk density and workability of concrete can be significantly improved. At the same time, the addition of modified silica fume can promote hydration reaction and improve the early strength and later performance of concrete.

[0073] Example 3: A method for preparing high performance concrete

[0074] The high performance concrete preparation method of this embodiment comprises the following steps:

[0075] (1) Preparation of fine admixture:

[0076] 90 parts by weight of 90-mesh slag powder, 22.5 parts by weight of 650-mesh kaolin, 8.75 parts by weight of 8000-mesh silica fume and 4.25 parts by weight of 250-mesh gypsum were mixed. The specific surface area of ​​the slag powder is 437.5 m 2 / kg, the specific surface area of ​​kaolin is 18.75m 2 / g, the specific surface area of ​​silica fume is 26.25m 2 / g. 8.75 parts by weight of water was added, and the mixture was dry-milled in a ball mill at a rotation speed of 237.5 rpm for 2.75 hours, and then wet-milled in a grinder at a rotation speed of 337.5 rpm for 1.75 hours. Finally, the mixture was dried at 75°C for 5.5 hours to obtain a fine admixture.

[0077] (2) Preparation of modified silica fume:

[0078] 100 parts by weight of SiO 2 Silica fume with a content of 92.5% was slowly added to 65 parts by weight of a sulfuric acid solution with a concentration of 98%, and stirred at 67.5°C for 1.75 hours. After cooling to room temperature, 13.75 parts by weight of γ-glycidyloxypropyltrimethoxysilane (KH-560) was added and stirred for 0.875 hours. The mixture was washed 3.75 times with 237.5 parts by weight of deionized water until the pH reached 5.75, and dried at 95°C for 7.5 hours to obtain modified silica fume.

[0079] (3) Preparation of ultrafine slag particles:

[0080] 100 parts by weight of a mixture containing 42.5% CaO, 42.5% SiO 2 37.5%, Al 2 O 3 A mixture of steel slag containing 10% Ag and 10% MgO and 237.5 parts by weight of zirconium balls and zirconium oxide balls was added to a planetary ball mill, dry-milled at a rotation speed of 387.5 rpm for 5.5 hours, sieved through a 45 μm sieve, and particles with a particle size of <45 μm were collected.

[0081] (4) Preparation of polyether polyol modified epoxy resin:

[0082] 100 parts by weight of polyacrylate polyol with a molecular weight of 1750, 8.75 parts by weight of sodium carbonate and 45 parts by weight of deionized water were mixed and stirred at 115°C for 3.5 hours. After cooling to 87.5°C, 27.5 parts by weight of glycidyl ether and 22.5 parts by weight of diethylenetriamine were added and stirred for 4.5 hours. The above product was mixed with 275 parts by weight of bisphenol A diglycidyl ether (DGEBA) and stirred for 5.5 hours at 145°C. The obtained product was mixed with 87.5 parts by weight of polypropylene glycol and stirred for 7.5 hours at 85°C. Finally, 27.5 parts by weight of glycidyl methacrylate were added at 67.5°C and the reaction was continued for 2.75 hours to obtain a polyether polyol modified epoxy resin.

[0083] (5) Preparation of high performance concrete:

[0084] 337.5 parts by weight of cement of strength grade 42.5, 187.5 parts by weight of fine admixture obtained in step (1), 637.5 parts by weight of coarse aggregate with a particle size of 16.25 mm, 537.5 parts by weight of fine aggregate with a particle size of 0.525 mm and 172.5 parts by weight of water were mixed and stirred in a mixer at a speed of 75 rpm for 52.5 seconds. 8.75 parts by weight of PVA fiber (0.55 dtex, 75 mm long) were added and stirred for 82.5 seconds. 4.5 parts by weight of polycarboxylic acid high-performance water reducer were added and stirred for 52.5 seconds. Finally, 17.5 parts by weight of polyether polyol modified epoxy resin obtained in step (4) were added and stirred for 112.5 seconds. The mixture was poured into a mold and vibrated on a vibration table at a frequency of 57.5 Hz for 56.25 seconds. High-performance concrete was obtained by curing for 28 days at 23.75°C and a relative humidity of 93.75%.

[0085] In the embodiments of the present invention, the addition of ultrafine steel slag particles can not only improve the strength of concrete, but also improve its microstructure and reduce porosity, thereby improving the durability of concrete. At the same time, the use of polyether polyol modified epoxy resin can significantly improve the interface bonding performance of concrete, and improve its crack resistance and impermeability.

[0086] Example 4: A method for preparing high performance concrete

[0087] The high performance concrete preparation method of this embodiment comprises the following steps:

[0088] (1) Preparation of fine admixture:

[0089] 100 parts by weight of 100-mesh slag powder, 25 parts by weight of 700-mesh kaolin, 10 parts by weight of 10,000-mesh silica fume and 5 parts by weight of 300-mesh gypsum were mixed. The specific surface area of ​​the slag powder is 450 m 2 / kg, the specific surface area of ​​kaolin is 20m 2 / g, the specific surface area of ​​silica fume is 30m 2 / g. 10 parts by weight of water was added, dry-milled in a ball mill at 250 rpm for 3 hours, and wet-milled in a grinder at 350 rpm for 2 hours. Finally, dried at 80°C for 6 hours to obtain a fine admixture.

[0090] (2) Preparation of modified silica fume:

[0091] 100 parts by weight of SiO 2 Silica fume with a content of 95% was slowly added to 70 parts by weight of a sulfuric acid solution with a concentration of 98%, and stirred at 70°C for 2 hours. After cooling to room temperature, 15 parts by weight of γ-glycidyloxypropyltrimethoxysilane (KH-560) was added and stirred for 1 hour. The mixture was washed 4 times with 250 parts by weight of deionized water until the pH reached 6, and dried at 100°C for 8 hours to obtain modified silica fume.

[0092] (3) Preparation of ultrafine slag particles:

[0093] 100 parts by weight of a mixture whose main chemical components are CaO 45%, SiO 2 30%, Al 2 O 3 Steel slag containing 15% of Ag and 10% of MgO and 250 parts by weight of zirconium oxide balls were added to a planetary ball mill and dry-milled at 400 rpm for 6 hours, sieved through a 45 μm sieve, and particles with a particle size of <45 μm were collected.

[0094] (4) Preparation of polyether polyol modified epoxy resin:

[0095] 100 parts by weight of polyacrylate polyol with a molecular weight of 2000, 10 parts by weight of sodium carbonate and 50 parts by weight of deionized water were mixed and stirred at 120°C for 4 hours. After cooling to 90°C, 30 parts by weight of glycidyl ether and 25 parts by weight of diethylenetriamine were added and stirred for 5 hours. The above product was mixed with 300 parts by weight of bisphenol A diglycidyl ether (DGEBA) and stirred at 150°C for 6 hours. The obtained product was mixed with 100 parts by weight of polypropylene glycol and stirred at 90°C for 8 hours. Finally, 30 parts by weight of glycidyl methacrylate were added at 70°C and the reaction was continued for 3 hours to obtain a polyether polyol modified epoxy resin.

[0096] (5) Preparation of high performance concrete:

[0097] Mix 350 parts by weight of cement of strength grade 42.5, 200 parts by weight of fine admixture obtained in step (1), 650 parts by weight of coarse aggregate with a particle size of 20 mm, 550 parts by weight of fine aggregate with a particle size of 0.6 mm and 180 parts by weight of water, and stir in a mixer at a speed of 80 rpm for 60 seconds. Add 10 parts by weight of PVA fiber (0.66 dtex, 80 mm long) and stir for 90 seconds. Add 5 parts by weight of polycarboxylic acid-based high-performance water reducer and stir for 60 seconds. Finally, add 20 parts by weight of polyether polyol-modified epoxy resin obtained in step (4) and stir for 120 seconds. Pour the mixture into a mold and vibrate it on a vibration table at a frequency of 60 Hz for 60 seconds. Curing for 28 days at 25°C and a relative humidity of 95% to obtain high-performance concrete.

[0098] The method for preparing high performance concrete further comprises the following steps:

[0099] The prepared high-performance concrete is poured into a formwork with a length of 3m. Adjacent formworks are connected with steel plates or angle steels. Tripods or temporary columns are added on the left and right sides of the formwork for support and fixed by adjusting cables. The formwork is retained at least 10cm outside the edges of the bottom surface of the concrete pouring bin on both sides, and the top of the formwork exceeds the upper edge of the pouring bin surface.

[0100] The pouring step comprises:

[0101] Use a concrete placing machine for pouring. The inclination angle between the concrete placing machine nozzle and the warehouse surface is 45°. The nozzle is 1.5m high from the warehouse surface. The lower edge of the nozzle is 0.5m away from the center line of the warehouse surface. Multiple nozzles are set on the conveying pipe of the concrete placing machine, and the nozzle arrangement spacing is 2m.

[0102] The material placing machine moves the material along the track at a speed of 0.5m / min, and adjusts the material placement position every 1.0m or so of material being unloaded.

[0103] In the embodiments of the present invention, by optimizing the proportions and preparation processes of each component, the overall improvement of concrete performance can be achieved. In particular, the multi-stage grinding process of fine admixtures can significantly improve its reactivity, the addition of modified silica fume can promote hydration reaction and pore structure optimization, ultrafine steel slag particles can improve the density and strength of concrete, and polyether polyol-modified epoxy resin can improve the interface bonding performance and crack resistance of concrete. This design concept of multi-component synergy enables the high-performance concrete of the present invention to reach excellent levels in terms of strength, durability, workability, etc.

[0104] Example 5

[0105] The high-performance concrete prepared by the preparation method of the high-performance concrete is used in the preparation of protective structural coatings, wherein the protective structural coatings contain 50-65% by weight of the high-performance concrete, 25-37% by weight of water, 1-6% by weight of acrylic latex, 0.1-1% by weight of a defoamer, 0.1-1% by weight of a dispersant, 0.1-1% by weight of a stabilizer and 0.1-1% by weight of a leveling agent.

[0106] These embodiments not only demonstrate the feasibility and flexibility of the method of the present invention, but also reflect the synergistic effect of the components in different proportions, providing rich references for practical applications.

[0107] Comparative Example 1: Conventional concrete preparation method

[0108] This comparative example is intended to be compared with Example 1 to verify the synergistic effect of the fine admixture and modified silica fume in the present invention.

[0109] The preparation method comprises the following steps:

[0110] (1) 350 parts by weight of cement of strength grade 42.5, 650 parts by weight of coarse aggregate with a particle size of 5 mm, 550 parts by weight of fine aggregate with a particle size of 0.3 mm, and 175 parts by weight of water were mixed and stirred in a mixer at a speed of 60 rpm for 60 seconds.

[0111] (2) Add 5 parts by weight of common water reducing agent and stir for 30 seconds.

[0112] (3) Pour the mixture into a mold and vibrate on a vibration table at a frequency of 50 Hz for 45 seconds.

[0113] (4) Curing for 28 days at 20°C and 90% relative humidity to obtain conventional concrete.

[0114] In this comparative example, due to the lack of fine admixtures and modified silica fume, the strength and durability of the concrete are relatively low. This is mainly because the pore structure of ordinary cement paste is relatively coarse, and the morphology and distribution of hydration products are not ideal, resulting in poor mechanical properties and impermeability of the concrete.

[0115] Comparative Example 2: Preparation method of single fine admixture concrete

[0116] This comparative example is intended to be compared with Example 2 to verify the synergistic effect of the multi-component fine admixtures in the present invention.

[0117] The preparation method comprises the following steps:

[0118] (1) Preparation of a single fine admixture:

[0119] 100 parts by weight of slag powder with a particle size of 75 mesh was dry-milled in a ball mill at a rotation speed of 225 rpm for 2.5 hours to obtain a single fine admixture.

[0120] (2) Preparation of concrete:

[0121] 325 parts by weight of cement of strength grade 42.5, 175 parts by weight of the single fine admixture obtained in step (1), 625 parts by weight of coarse aggregate with a particle size of 12.5 mm, 525 parts by weight of fine aggregate with a particle size of 0.45 mm and 165 parts by weight of water were mixed and stirred in a mixer at a speed of 70 rpm for 45 seconds. Subsequently, 4 parts by weight of a polycarboxylic acid-based high-performance water-reducing agent were added and stirred for 45 seconds. The mixture was poured into a mold and vibrated on a vibration table at a frequency of 55 Hz for 52.5 seconds. Cured for 28 days at 22.5° C. and a relative humidity of 92.5%, a single fine admixture concrete was obtained.

[0122] In this comparative example, due to the lack of kaolin, silica fume and gypsum, the performance improvement of concrete is limited. This is because the single slag powder cannot form an optimized particle size distribution, nor can it fully exert the potential of the pozzolanic reaction, resulting in insufficient improvement in the strength development and durability of the concrete.

[0123] Comparative Example 3: Preparation method of unmodified silica fume concrete

[0124] This comparative example is intended to be compared with Example 3 to verify the importance of modified silica fume in the present invention.

[0125] The preparation method comprises the following steps:

[0126] (1) Preparation of fine admixture:

[0127] The fine admixture was prepared in the same manner as in Example 3.

[0128] (2) Preparation of concrete:

[0129] 337.5 parts by weight of cement of strength grade 42.5, 187.5 parts by weight of fine admixture obtained in step (1), 637.5 parts by weight of coarse aggregate with a particle size of 16.25 mm, 537.5 parts by weight of fine aggregate with a particle size of 0.525 mm, 10 parts by weight of unmodified ordinary silica fume and 172.5 parts by weight of water were mixed and stirred in a mixer at a speed of 75 rpm for 52.5 seconds. 8.75 parts by weight of PVA fiber (0.55 dtex, 75 mm long) were added and stirred for 82.5 seconds. 4.5 parts by weight of polycarboxylic acid high-performance water reducing agent were added and stirred for 52.5 seconds. The mixture was poured into a mold and vibrated on a vibration table at a frequency of 57.5 Hz for 56.25 seconds. Unmodified silica fume concrete was obtained by curing at 23.75°C and a relative humidity of 93.75% for 28 days.

[0130] In this comparative example, due to the use of unmodified ordinary silica fume, its dispersibility and reactivity are low, which leads to uneven distribution of silica fume in concrete, reduced efficiency of volcanic ash reaction, and inability to fully exert its filling effect and role in promoting hydration reaction, ultimately affecting the strength development and microstructure optimization of concrete.

[0131] Comparative Example 4: Preparation method of concrete without ultra-fine steel slag particles

[0132] This comparative example is intended to be compared with Example 4 to verify the effect of the ultrafine steel slag particles in the present invention.

[0133] The preparation method comprises the following steps:

[0134] (1) Preparation of fine admixture and modified silica fume:

[0135] The fine admixture and modified silica fume were prepared in the same manner as in Example 4.

[0136] (2) Preparation of polyether polyol modified epoxy resin:

[0137] The same method as in Example 4 was used to prepare a polyether polyol modified epoxy resin.

[0138] (3) Preparation of concrete:

[0139] 350 parts by weight of cement of strength grade 42.5, 200 parts by weight of fine admixture obtained in step (1), 650 parts by weight of coarse aggregate with a particle size of 20 mm, 550 parts by weight of fine aggregate with a particle size of 0.6 mm, 15 parts by weight of modified silica fume obtained in step (1) and 180 parts by weight of water are mixed and stirred in a mixer at a speed of 80 rpm for 60 seconds. 10 parts by weight of PVA fiber (0.66 dtex, 80 mm long) are added and stirred for 90 seconds. 5 parts by weight of polycarboxylic acid high-performance water reducing agent are added and stirred for 60 seconds. Finally, 20 parts by weight of polyether polyol modified epoxy resin obtained in step (2) are added and stirred for 120 seconds. The mixture is poured into a mold and vibrated on a vibration table at a frequency of 60 Hz for 60 seconds. Cured for 28 days at 25°C and a relative humidity of 95% to obtain concrete without ultrafine steel slag particles.

[0140] In this comparative example, due to the lack of ultrafine steel slag particles, the density and strength of the concrete are limited. Ultrafine steel slag particles can not only fill the microscopic pores in the cement paste, but also participate in the hydration reaction to generate additional CSH gel. The lack of this component causes the microstructure of the concrete to be relatively loose, and the strength and durability are not significantly improved.

[0141] Comparative Example 5: Preparation method of epoxy resin concrete without polyether polyol modification

[0142] This comparative example is intended to be compared with Example 1 to verify the importance of the polyether polyol-modified epoxy resin in the present invention.

[0143] The preparation method comprises the following steps:

[0144] (1) Preparation of fine admixtures, modified silica fume and ultrafine steel slag particles:

[0145] The same method as in Example 1 was used to prepare fine admixtures, modified silica fume and ultrafine steel slag particles.

[0146] (2) Preparation of concrete:

[0147] 300 parts by weight of cement of strength grade 42.5, 150 parts by weight of fine admixture obtained in step (1), 600 parts by weight of coarse aggregate with a particle size of 5 mm, 500 parts by weight of fine aggregate with a particle size of 0.3 mm, 10 parts by weight of modified silica fume obtained in step (1), 20 parts by weight of ultrafine steel slag particles obtained in step (1) and 150 parts by weight of water are mixed and stirred in a mixer at a speed of 60 rpm for 30 seconds. 5 parts by weight of PVA fiber (0.22 dtex, 60 mm long) are added and stirred for 60 seconds. 3 parts by weight of polycarboxylic acid high-performance water reducing agent are added and stirred for 30 seconds. The mixture is poured into a mold and vibrated on a vibration table at a frequency of 50 Hz for 45 seconds. Cured for 28 days at 20°C and a relative humidity of 90% to obtain epoxy resin concrete without polyether polyol modification.

[0148] In this comparative example, due to the lack of polyether polyol modified epoxy resin, the interface bonding performance and crack resistance of the concrete are poor. This is mainly because the interface strength between the cement matrix and the aggregate and fiber is insufficient, and the performance of each component cannot be fully utilized, resulting in microcracks in the concrete during the stress process, affecting its overall performance and durability.

[0149] Comparative Example 6: Conventional mixing process concrete preparation method

[0150] This comparative example is intended to be compared with Example 2 to verify the importance of optimizing the stirring process in the present invention.

[0151] The preparation method comprises the following steps:

[0152] (1) Preparation of fine admixtures, modified silica fume, ultrafine steel slag particles and polyether polyol modified epoxy resin:

[0153] These components were prepared in the same manner as in Example 2.

[0154] (2) Preparation of concrete:

[0155] 325 parts by weight of cement of 42.5 strength grade, 175 parts by weight of fine admixture obtained in step (1), 625 parts by weight of coarse aggregate with a particle size of 12.5 mm, 525 parts by weight of fine aggregate with a particle size of 0.45 mm, 12.5 parts by weight of modified silica fume obtained in step (1), 25 parts by weight of ultrafine steel slag particles obtained in step (1), 165 parts by weight of water, 7.5 parts by weight of PVA fiber (0.44 dtex, 70 mm long), 4 parts by weight of polycarboxylic acid high-performance water reducing agent and 15 parts by weight of polyether polyol modified epoxy resin obtained in step (1) are added into a mixer at once and stirred continuously at a speed of 70 rpm for 5 minutes. The mixture is poured into a mold and vibrated on a vibration table at a frequency of 55 Hz for 52.5 seconds. Cured for 28 days at 22.5° C. and a relative humidity of 92.5%, a conventional mixing process concrete is obtained.

[0156] In this comparative example, due to the conventional mixing process of one-time addition, the components cannot be fully dispersed and reacted. This leads to agglomeration in the concrete, insufficient reaction of fine admixtures and modified silica fume, and uneven distribution of polyether polyol modified epoxy resin, which ultimately affects the overall performance and uniformity of the concrete.

[0157] Through these six comparative examples, we can clearly see the innovation and importance of the present invention in formulation design and preparation process, which not only proves the superiority of the present invention, but also provides a strong scientific basis for further optimization and application.

[0158] In order to comprehensively evaluate the performance and superiority of the high-performance concrete of the present invention, a series of test experiments were designed, covering multiple aspects such as material mechanics, durability and environmental adaptability. These experiments can not only verify the core innovation of the present invention, but also deeply explore the synergistic mechanism between the various components.

[0159] Experiment 1: Compressive strength test

[0160] Experimental conditions: in accordance with GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0161] Experimental steps:

[0162] 1. Prepare a cubic specimen of 100 mm × 100 mm × 100 mm.

[0163] 2. Curing under standard curing conditions (20±2℃, relative humidity above 95%) for 3 days, 7 days and 28 days.

[0164] 3. Use a pressure testing machine to perform compressive strength test at a loading rate of 0.5-0.8MPa / s.

[0165] 4. Test 3 specimens in each group and take the average value.

[0166] Experiment 2: Chloride Ion Permeability Test

[0167] Experimental conditions: Rapid chloride ion penetration test was carried out according to ASTM C1202.

[0168] Experimental steps:

[0169] 1. Prepare cylindrical specimens with a diameter of 100 mm and a thickness of 50 mm.

[0170] 2. After 28 days of curing under standard curing conditions, seal the sides with epoxy resin.

[0171] 3. Place the specimen in the test device with 3.0% NaCl solution on one side and 0.3 mol / L NaOH solution on the other side.

[0172] 4. Apply 60V DC voltage and test the amount of charge passing through the test piece within 6 hours.

[0173] Experiment 3: Freeze-thaw resistance test

[0174] Experimental conditions: in accordance with GB / T 50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete".

[0175] Experimental steps:

[0176] 1. Prepare a prism specimen of 100 mm × 100 mm × 400 mm.

[0177] 2. Cure for 28 days under standard curing conditions.

[0178] 3. Immerse the specimen in 5% NaCl solution and perform 300 freeze-thaw cycles (-18°C to 5°C).

[0179] 4. Measure the relative dynamic elastic modulus and mass loss every 50 cycles.

[0180] Experiment 4: Contraction performance test

[0181] Experimental conditions: refer to ASTM C157.

[0182] Experimental steps:

[0183] 1. Prepare prismatic specimens of 25 mm × 25 mm × 285 mm.

[0184] 2. Remove the mold after curing for 24 hours under standard curing conditions.

[0185] 3. Place the specimen in an environment with a temperature of 20±2℃ and a relative humidity of 50±4%.

[0186] 4. Length changes were measured at 1, 3, 7, 14, 28, 56 and 90 days.

[0187] Experiment 5: Sulfate corrosion resistance test

[0188] Experimental conditions: refer to GB / T 50082-2009.

[0189] Experimental steps:

[0190] 1. Prepare prism specimens of 40 mm × 40 mm × 160 mm.

[0191] 2. Cure for 28 days under standard curing conditions.

[0192] 3. Immerse the specimen in 5% Na2SO4 solution.

[0193] 4. Measure the mass change and relative dynamic elastic modulus at 30, 60, 90 and 180 days.

[0194] Based on the above experiments, Examples 1-4 and Comparative Examples 1-6 were fully tested, and the results are shown in the following table:

[0195] Table 1: Performance test results of various embodiments and comparative examples

[0196]

[0197] According to the test results, Example 4 performs best and can be regarded as the best embodiment of the present invention. Through comparative analysis, some unexpected technical effects of the present invention can be deeply explored:

[0198] 1. Ultra-high strength and excellent durability coexist: Generally speaking, high-strength concrete often faces the problem of insufficient durability, especially in terms of impermeability and crack resistance. However, the present invention, through the synergistic effect of multiple components, not only achieves a compressive strength of more than 100MPa, but also performs well in durability indicators such as chloride ion penetration, freeze-thaw cycles and sulfate erosion. This perfect combination of strength and durability breaks the trade-off relationship in traditional cognition.

[0199] 2. Significant self-repairing ability: Although the self-repairing performance was not directly tested, it can be inferred from the results of freeze-thaw cycles and sulfate attack that the concrete of the present invention has excellent self-repairing ability. This may be due to the secondary reaction of the polyether polyol modified epoxy resin at the microcracks and the continuous hydration of the ultrafine steel slag particles. This self-repairing ability can significantly extend the service life of the structure and reduce maintenance costs.

[0200] 3. Excellent dimensional stability: the free shrinkage rate in 90 days is only 302×10 -6, which is much lower than that of ordinary high-performance concrete. This excellent dimensional stability can be attributed to the synergistic effect of modified silica fume and ultrafine steel slag particles, which not only fill the microscopic pores but also form a more dense and stable microstructure through continuous hydration reaction and pozzolanic reaction.

[0201] 4. Comprehensive improvement of environmental adaptability: The concrete of the present invention has excellent performance in resistance to chloride ion penetration, freeze-thaw resistance and sulfate corrosion, which means that it has strong environmental adaptability. Especially in marine environments, cold regions and chemically corrosive environments, this concrete can exert advantages that other materials cannot match.

[0202] 5. Unification of process simplification and performance improvement: Through optimized mixing process, the present invention simplifies the production process while achieving full dispersion and reaction of each component. This not only improves the overall performance of concrete, but also reduces production difficulty and cost, laying the foundation for large-scale application.

[0203] These unexpected technical effects are derived from the synergistic mechanism of the components in the present invention:

[0204] 1. Synergy of modified silica fume and ultrafine steel slag particles: modified silica fume provides a large amount of active SiO 2 , while the ultrafine slag particles provide additional CaO. The two form more CSH gel during the hydration process, which not only improves the strength, but also optimizes the pore structure and improves durability.

[0205] 2. Interface strengthening effect of polyether polyol modified epoxy resin: This special resin not only improves the interface bonding of concrete, but also plays a "self-healing" role at micro-cracks, thereby improving the overall performance and durability of concrete.

[0206] 3. Optimization effect of multi-graded fine admixtures: Through the reasonable proportion of slag powder, kaolin, silica fume and gypsum, a multi-scale filling effect and multi-stage hydration reaction are formed, which not only improves the strength of concrete, but also significantly improves its workability and durability.

[0207] 4. The key role of optimizing the mixing process: The step-by-step, time-controlled mixing process ensures the full dispersion and reaction of each component, maximizing the performance advantages of each material.

[0208] In summary, the present invention achieves a comprehensive breakthrough in the strength, durability and environmental adaptability of high-performance concrete through the synergistic effect of multiple components and optimized preparation process, providing a revolutionary material solution for future infrastructure construction and special environmental applications.

[0209] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing high performance concrete, characterized in that: The following steps are involved: (1) Preparation of fine admixture: 50-100 parts by weight of slag powder with a particle size of 50-100 mesh, 15-25 parts by weight of kaolin with a particle size of 500-700 mesh, 5-10 parts by weight of silica fume with a particle size of 3000-10000 mesh and 2-5 parts by weight of gypsum with a particle size of 100-300 mesh are mixed, 5-10 parts by weight of water are added, dry-milled in a ball mill at a rotation speed of 200-250 rpm for 2-3 hours, then wet-milled in a grinder at a rotation speed of 300-350 rpm for 1-2 hours, and finally dried at 60-80° C. for 4-6 hours to obtain a fine admixture; (2) Preparation of modified silica fume: Slowly add 100 parts by weight of silica fume to 50-70 parts by weight of a 98% sulfuric acid solution, stir and react at 60-70°C for 1-2 hours, cool to room temperature, add 10-15 parts by weight of γ-glycidyloxypropyltrimethoxysilane, continue stirring for 0.5-1 hour, wash 3-4 times with 200-250 parts by weight of deionized water until the pH reaches 5-6, and dry at 80-100°C for 6-8 hours to obtain modified silica fume; (3) Preparation of ultrafine slag particles: 100 parts by weight of steel slag and 200-250 parts by weight of zirconium balls or zirconium oxide balls are added to a planetary ball mill, dry-milled at a speed of 350-400 rpm for 4-6 hours, sieved through a 45 μm sieve, and particles with a particle size of <45 μm are collected; (4) Preparation of polyether polyol modified epoxy resin: First, 100 parts by weight of polyacrylate polyol with a molecular weight of 1000-2000, 5-10 parts by weight of sodium carbonate and 30-50 parts by weight of deionized water are mixed, and stirred at 100-120° C. for 2-4 hours; Secondly, cool to 80-90°C, add 20-30 parts by weight of epoxy crosslinking agent and 15-25 parts by weight of polyamine crosslinking agent, and continue stirring and reacting for 3-5 hours; Then, the above product is mixed with 200-300 parts by weight of bisphenol A diglycidyl ether, and stirred at 130-150° C. for 4-6 hours; Again, the obtained product is mixed with 50-100 parts by weight of polyether polyol with a molecular weight of 1000-3000, and stirred at 70-90° C. for 6-8 hours; Finally, adding 20-30 parts by weight of glycidyl methacrylate at 60-70° C. and continuing the reaction for 2-3 hours to obtain a polyether polyol modified epoxy resin; (5) Preparation of high performance concrete: Mix 300-350 parts by weight of cement, 42.5 strength grade, 150-200 parts by weight of the fine admixture obtained in step (1), 600-650 parts by weight of coarse aggregate with a particle size of 5-20 mm, 500-550 parts by weight of fine aggregate with a particle size of 0.3-0.6 mm and 150-180 parts by weight of water, and stir in a mixer at a speed of 60-80 rpm for 30-60 seconds; Add 5-10 parts by weight of PVA fiber, 0.22-0.66 dtex, 60-80 mm long, and stir for 60-90 seconds; Add 3-5 parts by weight of polycarboxylic acid high performance water reducer and stir for 30-60 seconds; Finally, add 10-20 parts by weight of the polyether polyol modified epoxy resin obtained in step (4) and stir for 90-120 seconds; Pour the mixture into a mold and vibrate on a vibration table at a frequency of 50-60 Hz for 45-60 seconds; The high performance concrete is obtained by curing for 28 days under the conditions of 20-25°C and relative humidity of 90-95%.

2. The method for preparing high performance concrete according to claim 1, characterized in that: In step (1), the specific surface area of ​​the slag powder is 400-450m 2 / kg, the specific surface area of ​​the kaolin is 15-20m 2 / g, the specific surface area of ​​the silica fume is 15-30m 2 / g.

3. The method for preparing high performance concrete according to claim 1, characterized in that: In the step (2), the SiO2 content of the silica ash is ≥85%.

4. The method for preparing high performance concrete according to claim 1, characterized in that: In the step (3), the main chemical components of the steel slag are CaO 35-45%, SiO2 30-40%, Al2O3 10-15% and MgO 5-10%.

5. The method for preparing high performance concrete according to claim 1, characterized in that: In the step (4), the trade name of the polyacrylate polyol is Desmophen 1150 or Fomrez 55-112, the epoxy crosslinking agent is glycidyl ether, the trade name is Epikote 828 or DER 331, and the polyamine crosslinking agent is diethylenetriamine, the trade name is DETA or Duomeen O.

6. The method for preparing high performance concrete according to claim 1, characterized in that: In the step (4), the polyether polyol is polypropylene glycol, and its trade name is Voranol or Jeffol.

7. The method for preparing high performance concrete according to claim 1, characterized in that: In the step (5), the trade name of the polycarboxylic acid-based high-performance water reducer is MasterGlenium or Sika ViscoCrete.

8. The method for preparing high performance concrete according to any one of claims 1 to 7, characterized in that: The following steps are also included: The prepared high-performance concrete is poured into a formwork with a length of 3m. Adjacent formworks are connected with steel plates or angle steels. Tripods or temporary columns are added on the left and right sides of the formwork for support and fixed by adjusting cables. The formwork is retained at least 10cm outside the edges of the bottom surface of the concrete pouring bin on both sides, and the top of the formwork exceeds the upper edge of the pouring bin surface.

9. The method for preparing high performance concrete according to claim 8, characterized in that: The pouring step comprises: Use a concrete placing machine for pouring. The inclination angle between the concrete placing machine nozzle and the warehouse surface is 45°. The nozzle is 1.5m high from the warehouse surface. The lower edge of the nozzle is 0.5m away from the center line of the warehouse surface. Multiple nozzles are set on the conveying pipe of the concrete placing machine, and the nozzle arrangement spacing is 2m. The material placing machine moves the material along the track at a speed of 0.5m / min, and adjusts the material placement position every 1.0m or so of material being unloaded.

10. Use of high performance concrete prepared by the method for preparing high performance concrete according to any one of claims 1 to 9 in preparing protective structural coatings, characterized in that: The protective structural coating comprises 50-65 wt % of the high performance concrete, 25-37 wt % of water, 1-6 wt % of acrylic latex, 0.1-1 wt % of a defoamer, 0.1-1 wt % of a dispersant, 0.1-1 wt % of a stabilizer and 0.1-1 wt % of a leveling agent.